Study of Rare Mesonic Decays Involving Di-Neutrinos in Their Final State - Azeem Mir; Farida Tahir; Shakeel Mahmood; Shi- Hai Dong (Advances in High Energy Physics)
We have studied phenomenological implication of R-parity violating (Rp) Minimal Supersymmetric Model (MSSM) via analyses of pure leptonic (M→νν¯) and semileptonic decays of pseudoscalar mesons (M→Xνν¯). These analyses involve comparison between theoretical predictions made by Rp MSSM and the Standard Model (SM) with the experimental results like branching fractions (Br) of the said process. We have found, in general, that Rp contribution dominates over the SM contribution, i.e., by a factor of 10 for the pure leptonic decays of KL,S and by 102 and 104 in case of Bs and Bd, respectively. Furthermore, the limits obtained on Rp Yukawa couplings (λαkβ′λαkγ′⁎) by using Br  (M→Xνν¯) are used to calculate Br  (M→νν¯). This demonstrates the role of Rp MSSM as a viable model for the study of new physics contribution in rare decays at places like Super B factories, KOTO (J-PARC) and NA62 at CERN.